Kepadatan Makrozoobentos pada Wilayah Penangkapan Kerang Anadara spp. Di Perairan Teluk Lada Selat Sunda, Pandeglang Banten - ajeng daniarsih (Universitas Negeri Malang, 2021)
Environmental parameters and human activities around the waters can affect the growth and density of macrozoobentos. The aim of this study is to know the density, composition, diversity, uniformity, dominance and distribution patterns as well as physical and chemical factors that influence the life aquatic macrozoobentos. The study was conducted at the waters of the Lada Gulf, Sunda Strait, Pandeglang Banten. This research is descriptive method with survey technique the determination of station and taking sample purposive sampling. Location of this study were divided into 3 zones (Bama Beach, Cibungur Beach and Panimbang Beach), each zone is divided into three station. Analysis include density and diversity index. The results showed 27 species identified with the highest density and composition represented by Anadara granosa amounted to 9 ind/m2 and 32.27%, while the lowest density is Distorsia reticulata at 0,011 ind/m2 with 0.04% of the composition. Temporally, the highest density of macrozoobentos occurred in August and lowest in July, the highest spatial zone I and lowest in zone II.